Cryptogenic Organizing Pneumonia During Adjuvant Chemotherapy With Oxaliplatin, 5-Fluorouracil, and Leucovorin (FOLFOX) for Colon Cancer. (February 2013) - Shogbon, Angela O.; Hap, Jenna; Dretler, Robin; Dalvi, Anant G.
Lung disease associated with FOLFOX (oxaliplatin/5-fluorouracil/leucovorin) chemotherapy is uncommon. We describe a case of cryptogenic organizing pneumonia (COP) occurring in a 78-year-old woman after receiving 2 cycles of modified FOLFOX6 as adjuvant chemotherapy for treatment of resected nonmetastatic colon cancer. This patient presented with respiratory symptoms including cough with scant clear sputum and wheezing on day 10 of the second cycle of mFOLFOX6. Despite therapy with systemic antibiotics and supplemental oxygen, she had a steady and relentless progression of her respiratory symptoms and status, with chest radiographs revealing progressive bilateral pulmonary infiltrates. Further chest radiograph evaluation demonstrated findings consistent with COP. Antibiotics were discontinued and methylprednisolone sodium succinate initiated as the mainstay of management for COP. The patient required a higher dose of methylprednisolone sodium succinate than typical for initial response with doses up to 3 mg/kg per d leading to prompt improvement in her respiratory symptoms and function and declining need for supplemental oxygen therapy. Chest radiographs also showed improvement. The Naranjo adverse drug reaction probability scale indicated a probable relationship (score of 5) between the patient's COP and the FOLFOX chemotherapy. Clinicians should be aware of the potential for this uncommon, yet severe adverse reaction associated with the FOLFOX chemotherapy.